Immunisation of cattle with cysteine proteinases of Trypanosoma congolense: Targetting the disease rather than the parasite - Authié, Edith; Boulange, A.F.; Muteti, D.; Lalmanach, G.; Gauthier, F.; Musoke, A.J. (Elsevier, 2001)
In order to test the hypothesis that trypanosome cysteine proteinases (CPs) contribute to pathology of trypanosomosis. cattle were immunised with CPl and/or CP2, the major Cps of Trypanosoma congolense, and subsequently challenged with T. congolense. Immunisation had no effect on the establishment of infection and the development of acute anaemia. However, immunised cattle, unlike control cattle, maintained or gained weight during infection. Their haematocrit and leukocyte counts showed a tendency to recovery after 2-3 months of infection. Cattle immunised with CP2 mounted early and prominent IgG responses to CPs and to the variable surface glycoprotein following challenge. Thus trypanosome CPs may play a role in anaemia and immunosuppression; conversely, anti-CP antibody may modulate the trypanosome-induced pathology.